Professional Accounting Body Affiliation: Shifting Priorities in the Transition from Student to Practitioner - Sidaway, S.; De Lange, Paul; Bouilheres, F.; Sangster, A. (Routledge, 2013)
Extending the scope of prior research, this study examines perceptions of the costs and benefits of professional accounting body affiliation in the transition from student to practitioner. The study employs data obtained from 275 students and 508 practitioners and reports differences in respect of the importance placed on various costs and benefits associated with affiliation. Findings show it is important to avoid a ‘one-size-fits-all’ approach to attracting and retaining members and that the needs and aspirations of tomorrow’s accountants are different from those of experienced professional accountants. Implications for brand development and member recruitment and retention strategies are discussed.